Redescriptions of three species in the louse genus Myrsidea (Insecta: Phthiraptera: Amblycera) - Schneider, Marek; Kolencik, Stanislav; Literak, Ivan; Sychra, Oldrich (Zootaxa, 2025)
Three species of chewing lice in the genus Myrsidea are redescribed and illustrated. They are: Myrsidea aegithali Blagoveshtchensky, 1940 from Aegithalos caudatus alpinus (Hablizl, 1783); Myrsidea flavida (Piaget, 1880) from Eurylaimus ochromalus Raffles, 1822; and Myrsidea franciscoloi Conci, 1942 from Cinclus cinclus (Linnaeus, 1758). These species are like “type species”, characterising three groups of morphotypes. Redescriptions are made from the type material. Lectotype and paralectotypes are designated for M. aegithali. We increase knowledge of the intraspecific morphological variability of these species, including phylogenetically informative characteristics, and a new host association for M. aegithali from Aegithalos concinnus.